Sea Blue Histiocytosis Secondary to Niemann Pick Disease - Dodhy, Mobina Ahsan; Aslam, Wardah; Nazir, Amna; Shaheen, Masooma; Habib, Maryam (International Journal of Pathology, 2018)
Sea blue histiocytosis is a rare disorder, characterized by the presence of atypical macrophages (seablue histiocytes) in the bonemarrow detectable by May-Giemsa staining. We report a case of a 3 years old female,whose bone marrow examination revealed numerous sea blue histiocytes and Niemann-Pick cells (storage cells).Niemann-Pick disease is the most common cause of secondary sea-blue histiocytosis.